Anxiety and Depression Among Students with Intellectual and Developmental Disabilities in Lahore, Pakistan: A Quantitative Study - Muhammad Noman Maqbool; Mubara Sehar (JIE, 2025)
This study investigates the prevalence of anxiety and depression among students with intellectual and developmental disabilities (IDD) in Lahore, Pakistan, a region where limited research exists on the mental health of this vulnerable group. Given the unique challenges faced by individuals with IDD, understanding their mental health needs is critical for ensuring appropriate care and support. Using a quantitative research approach, data were collected from 32 teachers working in various schools that cater to students with intellectual and developmental disabilities. The data collection involved structured surveys that assessed the mental health status of students as observed by their educators, with a particular focus on symptoms related to anxiety and depression. The findings highlight significant concerns regarding the mental health of these students, revealing that a substantial proportion exhibit symptoms of anxiety and depression, which can severely impact their overall well-being, academic performance, and social integration. The study provides valuable insights into the specific environmental, social, and educational factors that may contribute to the prevalence of these mental health conditions among students with IDD in Lahore. These factors include limited mental health awareness among teachers, lack of specialized mental health services, and societal stigma surrounding both disabilities and mental health challenges.